An exploratory study of the relationship between store-related stimuli and consumers' price-quality-value perceptions - Lee, Dorothy Jing (2014)
Much research has been done to identify the underlying constructs that influence consumers’ value perceptions of supermarkets. This exploratory study aims to investigate the relationship between store-related stimuli and the consumer’s perception of price, quality and value in the local supermarket scene e.g., Cold Storage, NTUC Fairprice and Yaohan. Various important store attributes have been identified to provide an insight into how retailers can differentiate their supermarkets from competitors.